(untitled) (Bulletin KNOB, 2003)
No doubt the intention was good. However, the result turned out much less favourably. In the year 1996 the cement-rustic bridge at Bochtdijk in the park of De Haar Castle was restored. It had the appearance of a bridge made of tree-trunks, a frequently used technique in the nineteenth century and the beginning of the twentieth century. It looked as if a lorry had bumped into it a very long time ago, and had damaged the right-hand side. However, the iron in the cement may have started to ’work’, a frequently occurring problem. The ’restoration’ was very rigorous indeed. The bridge itself ended up in a large container, while a building firm was constructing a new bridge in a similar style. An utterly wrong approach, making the bridge completely useless as a bearer of information on a historical building technique. In principle, it also made identification of the workshop that had built this bridge impossible. The starting point of the ’restoration’ was the general appearance of the bridge, but evidently the builders were not acquainted with the subtleties of cement-rustic, a nineteenth-century style that had not been documented in detail yet. For the crux is the representation of the ’tree-bark’ grains, which is the signature of every cement-rustic builder, called ’rocailleur’ in France and Wallonia and ’rotseerder’ in Flanders. The plasterer who gave the new bridge its present appearance, though an expert in his trade, could not have known this. But the commissioner should have, or should at least have given instructions for expert research. This was omitted, and that is why the cement-rustic bridge as a historical object was lost to us. It subsequently appeared that the bridge was a product of the firm F.J. Moerkoert from De Bilt. And a long story is attached to this.